2020
DOI: 10.21037/atm.2020.01.10
|View full text |Cite
|
Sign up to set email alerts
|

Sirolimus-based immunosuppression improves outcomes in liver transplantation recipients with hepatocellular carcinoma beyond the Hangzhou criteria

Abstract: Background: The administration of calcineurin inhibitors (CNIs) posttransplant has been implicated as an independent risk factor for the recurrence of hepatocellular carcinoma (HCC) after liver transplantation (LT). The new immunosuppressive agent sirolimus (SRL) acts as a primary immunosuppressant or antitumor agent. In this study we investigated the effect of sirolimus-based immunosuppression compared to CNIs (non-SRL) on the outcomes of LT candidates with HCC.Methods: We retrospectively analyzed 204 HCC pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Using mTOR inhibitors for at least 3 months after LT for HCC independently reduced the death rate by approximately 30%. Our retrospective study also revealed that patients with a higher tumor burden could achieve a greater survival benefit from sirolimus use after LT 11 . However, given the complicated molecular mechanisms underlying cancer progression, drug resistance is hard to avoid upon targeting the mTOR pathway alone 3 .…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Using mTOR inhibitors for at least 3 months after LT for HCC independently reduced the death rate by approximately 30%. Our retrospective study also revealed that patients with a higher tumor burden could achieve a greater survival benefit from sirolimus use after LT 11 . However, given the complicated molecular mechanisms underlying cancer progression, drug resistance is hard to avoid upon targeting the mTOR pathway alone 3 .…”
Section: Introductionmentioning
confidence: 75%
“…9 mTOR inhibitors, sirolimus and everolimus, are widely used as an immunosuppressant after LT. A recent study based on the SiLVER trial (Clini caltr ials.gov: NCT00355862) emphasized the antitumor effect of mTOR inhibitors in patients with HCC after LT. 10 Using mTOR inhibitors for at least 3 months after LT for HCC independently reduced the death rate by approximately 30%. Our retrospective study also revealed that patients with a higher tumor burden could achieve a greater survival benefit from sirolimus use after LT. 11 However, given the complicated molecular mechanisms underlying cancer progression, drug resistance is hard to avoid upon targeting the mTOR pathway alone. 3 It is of great importance to explore the resistance mechanisms to mTOR inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 1080 full‐text articles were identified and assessed for eligibility. Finally, based on the inclusion and exclusion criteria, 38 articles involving 10,607 HCC patients were included in our meta‐analysis 8–45 …”
Section: Methodsmentioning
confidence: 99%
“…Pooled risk ratios: primary outcome (recurrence rate, overall mortality) A total of 22 studies [8][9][10][11][12][13][14]17,19,23,25,28,29,33,[35][36][37][38][39][40][41] (6548 subjects) reported recurrence rates. Meta-analysis demonstrated a significant improvement in the recurrence rate with mTORi therapy (RR: .78, 95% CI: .68-.89).…”
Section: 4mentioning
confidence: 99%
“…RAPA can also have anti-tumor effects by inhibiting tumor cell proliferation and angiogenesis while exerting immunosuppressive effects. RAPA conversion can effectively reduce the risk of post-LT HCC recurrence and prolong the tumor-free survival time of patients during different studies[ 40 , 41 ]. Subsequently, meta-analysis affirmed to varying degrees the survival benefit of RAPA in HCC patients after LT, but these studies have their limitations because of single-center experience[ 11 , 42 , 43 ].…”
Section: Trends Of Rapa In Survival Benefits Of Transplant For Hccmentioning
confidence: 99%